Analysis of cold-start NO2 and NOx emissions, and the NO2/NOx ratio in a diesel engine powered with different diesel-biodiesel blends. (1st December 2021) - Zare, Ali; Stevanovic, Svetlana; Jafari, Mohammad; Verma, Puneet; Babaie, Meisam; Yang, Liping; Rahman, M.M.; Ristovski, Zoran D.; Brown, Richard J.; Bodisco, Timothy A.
Abstract: In the transportation sector, the share of biofuels such as biodiesel is increasing and it is known that such fuels significantly affect NOx emissions. In addition to NOx emission from diesel engines, which is a significant challenge to vehicle manufacturers in the most recent emissions regulation (Euro 6.2), this study investigates NO2 which is a toxic emission that is currently unregulated but is a focus to be regulated in the next regulation (Euro 7). This manuscript studies how the increasing share of biofuels affects the NO2, NOx, and NO2 /NOx ratio during cold-start (in which the after-treatment systems are not well-effective and mostly happens in urban areas). Using a turbocharged cummins diesel engine (with common-rail system) fueled with diesel and biofuel derived from coconut (10 and 20% blending ratio), this study divides the engine warm-up period into 7 stages and investigates official cold- and hot-operation periods in addition to some intermediate stages that are not defined as cold in the regulation and also cannot be considered as hot-operation. Engine coolant, lubricating oil and exhaust temperatures, injection timing, cylinder pressure, and rate of heat release data were used to explain the observed trends. Results showed that cold-operation NOx, NO2, and NO2 /NOx ratio were 31–60%, 1.14–2.42 times, and 3–8% higher than the hot-operation, respectively. In most stages, NO2 and the NO2 /NOx ratio with diesel had the lowest value and they increased with an increase of biofuel in the blend. An injection strategy change significantly shifted the in-cylinder pressure and heat release diagrams, aligned with the sudden NOx drop during the engine warm-up. The adverse effect of cold-operation on NOx emissions increased with increasing biofuel share. Graphical abstract: Image 1 Highlights: Cold-operation NOx was 31–60% higher than hot-operation with different fuels. Cold-operation adverse effect on NOx was more with biofuel. Cold-operation NO2 was 1.15–2.42 times higher than hot-operation with all fuels. Cold-operation NO2 /NOx was 3–8% higher than hot-operation with different fuels. NO2 /NOX ratio was 13–17% during cold-operation and 5–13% during hot-operation.